Konsep Imam dan Jabatan Imam pada Masa Intertestamental - Paulus Kunto Baskoro (Sekolah Tinggi Teologi Berita Hidup, 2020)
ABSTRACTThe intertestamental period is a Protestant term, while the deuterocanonical period is a Catholic and Orthodox Christian term to refer to the time gap between the period covered by the Hebrew Bible or